Síntese e avaliação da atividade biológica de alcaloides e derivados n-heterociclos - Duarte, Patricia Domingos (2013)
4-Quinolinone derivatives and hydantoins are important classes of cyclic nitrogen compounds which have very interesting biological activity against a variety of biological targets. Phytochemical studies of plants of the genus Dictyoloma, guided by in vitro bioassays, led to the isolation of three new 4-quinolinone alkaloids, the dictyolomides A and B and 6- methoxydictyolomide, which showed good activity against Leishmania. The absolute configuration of the natural dictyolomides is still unkown. This work aimed the asymmetric synthesis of these alkaloids. In order to introduce the enantiomeric enriched side chains in the 4-quinolinone core, some synthetic routes have been tested employing organometallic chemistry, among other techniques. A series of 4-quinolinone derivatives was also synthesized, using methods described in the literature, especially the one described by Ding et al., in which it uses microwave irradiation. The study of the synthesis of hydantoin derivatives was also performed using microwave irradiation as a source of energy. New organocatalysts were tested in order to obtain new amino acid derivatives which would be employed as starting materials in the synthesis of hydantoins. The synthesized compounds were submitted to bioassays focus on antiparasitic activity and enzyme inhibition. The result obtained with 4- quinolinone derivatives against proliferation of Leishmania amazonensis promastigotes and epimastigotes of Trypanosoma cruzi showed that the compounds possess in general better leishmanicidal than trypanocidal activity. Nevertheless, two of the synthesized compounds showed an excellent trypanocidal activity, even better than the standard, benznidazole. The 4- quinolinones have also shown good inhibitory activity against cathepsin L and V enzymes.